ANALYSIS OF FOOD SECURITY AND SELF-SUFFICIENCY IN FOOD IN SOUTH SULAWESI - Sjamsir, Zulkifli; Besse Dahliana; Suhartina R (PT. Jurnal Center Indonesia Publisher, 2025)
This study examines food security, food self-sufficiency, and self-sufficiency in South Sulawesi in 2024, focusing on the province's main food commodities, distribution issues, and the impact of government policies. The research analyzes the gap between food production and demand, identifying key commodities such as rice, corn, and soybeans. By evaluating the availability, accessibility, and affordability of these staple foods, the study investigates how local agricultural practices, infrastructure, and external factors like climate change and market volatility affect food security in the region. The findings reveal significant challenges in meeting the demand for rice and soybeans, despite the province's ability to achieve a surplus in corn production. The methodology employed in this study involves both qualitative and quantitative approaches. Primary data was gathered through field surveys, interviews with local farmers, agricultural experts, and policymakers, as well as secondary data from government reports, agricultural statistics, and market analyses. A comparative analysis was conducted to examine trends in food production, consumption patterns, and price fluctuations over the past five years. The study also incorporated geographic information system (GIS) mapping to assess the distribution of agricultural resources and the effectiveness of existing infrastructure in connecting farmers to markets. The findings suggest that despite the province's agricultural potential, South Sulawesi continues to face challenges in achieving full food self-sufficiency. The study recommends a multifaceted approach to addressing food insecurity and achieving food self-sufficiency, including improving rural infrastructure, adopting modern agricultural technologies, and diversifying food crops.